2021
DOI: 10.1049/ipr2.12268
|View full text |Cite
|
Sign up to set email alerts
|

Image resolution and contrast enhancement with optimal brightness compensation using wavelet transforms and particle swarm optimization

Abstract: Improving the image resolution and contrast along with uniform brightness distribution over the entire image helps to retrieve the vital realistic information necessary for human perception and interpretation. A new procedure to improve these parameters is implemented and tested. Initially, the image is super resolute using discrete wavelet transform (DWT), stationary wavelet transform (SWT) image decomposition and bicubic interpolation. The resolute image is used for contrast enhancement by using SWT and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This framework first generates multiple artificially multi-exposure images using a mapping function, then combines exposure to create a weight map, and finally fuses different frequency bands of the image. Testing outcomes showed that this method outperforms existing algorithms in enhancing low-light images [9]. Lu et al believed that the current image enhancement methods based on convolutional neural network models do not differentiate image features on different channels, which hinders the learning of hierarchical features.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…This framework first generates multiple artificially multi-exposure images using a mapping function, then combines exposure to create a weight map, and finally fuses different frequency bands of the image. Testing outcomes showed that this method outperforms existing algorithms in enhancing low-light images [9]. Lu et al believed that the current image enhancement methods based on convolutional neural network models do not differentiate image features on different channels, which hinders the learning of hierarchical features.…”
Section: Literature Reviewmentioning
confidence: 98%
“…However, due to the limitations of low-light environments, Chinese paintings in low-light scenes may face the problem of uneven pigment brightness, which affects the visibility and artistic quality of the artwork to some extent. A low-light environment refers to an environment with dim lighting or insufficient light sources [2]. In such environments, due to the scarcity and weakening of light, details in the image are difficult to display clearly, and the differences in pigment brightness become more pronounced.…”
Section: Introductionmentioning
confidence: 99%
“…After 𝐽-level decomposition of the micro-animation video image, 8𝐽 + 1 sub-images will be obtained, that is, the expression of the image in the wavelet domain is [12] :…”
Section: Image Denoising Processingmentioning
confidence: 99%
“…Luque_Chang et al 30 have introduced Moth Swarm Algorithm (MSA) for image contrast enhancement. Other optimization algorithms have also been used such as Artificial bee colony (ABC), 5 Barnacles Mating Optimizer (BMO), 2 Genetic algorithm (GA), 1 Social spider optimization algorithm (SSOA), 33 and Particle swarm optimization (PSO) 53 …”
Section: Introductionmentioning
confidence: 99%
“…Other optimization algorithms have also been used such as Artificial bee colony (ABC), 5 Barnacles Mating Optimizer (BMO), 2 Genetic algorithm (GA), 1 Social spider optimization algorithm (SSOA), 33 and Particle swarm optimization (PSO). 53 The MPA 15 was a recently proposed meta-heuristic algorithm. So far, this algorithm has been effectively applied in many applications, such as medical image synthesis, 9 multilevel image segmentation, 32 and fault diagnosis of rolling bearing.…”
mentioning
confidence: 99%